Wideband waveform generation using MDDS and phase compensation for X-Band SAR - Kim, Kyeong Rok; Kim, Jae Hyun (Remote Sensing, 2020)
This study investigated wideband waveform generation using a field programmable gate array (FPGA) for X-band high-resolution synthetic aperture radar (SAR). Due to the range resolution determined by the bandwidth, we focused on wide bandwidth generation while preserving spectrum quality. The proposed method can generate wide bandwidth using a relatively low system clock. The new approach was designed in Simulink and implemented by very-high-speed-integrated-circuits hardware description language (VHDL). We also proposed a hardware structure in accordance with the proposed method. Signal connections of FPGA and digital analog converter (DAC) are described in the design of the proposed hardware structure. The developed X-band waveform generator using the proposed method output the desired pulse waveform. For the reduction of phase error and improvement of spectrum quality at the X-band, phase error compensation and pre-distortion were applied to the waveform generator. The results of the simulation and the hardware output demonstrate that the variation and standard deviation of the phase error were improved within the frequency spectrum. Accordingly, the proposed method and the developed waveform generator have the potential to produce a high-resolution image of the area of interest.
Keywords: Digital analog converter (DAC); Hardware structures; High resolution image; High resolution synthetic aperture radar; Phase error compensations; Spectrum qualities; Very high speed integrated circuits; Waveform generators; FPGA; Multi-DDS; SAR; Wideband; X-band